Parkinson Disease: A Review - Kumari, Annu; Gupta, Muskan; Rankawat, Gaurav; Rankawat, Abhishek (Asian Journal of Pharmaceutical Research and Development, 2023)
Parkinson disease is a neurodegenerative progressive disorder which caused due to increase level of Ach and lack of dopamine inside the brain. The dopaminergic cell death were found inside the brain in case of Parkinson disease. It’s a type of motor deficiency disease. Many symptoms like bradykinesia, tremor, postural instability, loss of sense of smell etc. are arises in Parkinson disease and there is no specific cure for Parkinson. A molecular biomarker is important to find because it differentiate the Parkinson from other disease and this disease mainly consultant by the neurologist. The management and treatment of Parkinson disease is based on some drugs, like levodopa, dopamine agonist, MAO-beta inhibitor, CoMT inhibitors and many more. They are used with or without in combination and Parkinson include various risk factor like herbicides, pesticides, metal exposure etc. Various type of surgical approaches. Deep brain stimulation are good for Parkinson patients. Nicotine, caffeine, hormone replacement therapy are the some protective factors which overcome the chances of Parkinson disease.